PENGARUH PENERIMAAN DIRI (SELF-ACCEPTANCE) SANTRI TERHADAP KEPATUHAN (OBEDIENCE) PADA PERATURAN PESANTREN - Ajmelia Savira (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2023)
Islamic boarding school regulations are made to be obeyed in the hope that the students can live by the commendable norms of Islamic boarding schools. However, in reality, many students do not heed these regulations. To help increase student obedience with Islamic boarding school regulations, good self-acceptance is needed for each individual. For this reason, researchers feel it is necessary to study the influence of students’ self-acceptance on obedience with Islamic boarding school regulations. This research aims to find out two things: 1) Can students’ self-acceptance influence obedience with Islamic boarding school regulations? 2) How big is the influence of student’ self-acceptance on obedience with Islamic boarding school regulations? To answer this, the researcher used a quantitative correlation approach. This research is located at PP. Annuqayah Lubangsa Selatan Putri with a sample size of 31 people from a population of 307. The researcher did not provide specific criteria for the sample, because all populations have the same potential. Research data was obtained from distributing questionnaires using a simple random sampling technique and the analysis process by testing hypotheses using a simple linear regression test with the prerequisites that the data must be valid, reliable, normally distributed and linear. The final result of the research show that students’ self-acceptance has a positive effect on obedience with Islamic boarding school regulations with a Pearson correlation value of 0,466 and the participation of students’ self-acceptance in increasing obedience with Islamic boarding school regulations is 21,7 %.